A nationwide case-referent study on elevated risks of adenocarcinoma lung cancer by long-term PM2.5 exposure in Taiwan since 1997 - Lin, Wei-Chi; Shie, Ruei-Hao; Yuan, Tzu-Hsuen; Tseng, Chien-Hua; Chiang, Chun-Ju; Lee, Wen-Chung; Chan, Chang-Chuan (Environmental research, 2024)
The effects of long-term PM2.5 exposures since 1968 on adenocarcinoma lung cancer (AdLC) were not studied before. This case-referent study used nationwide cancer registry data since 1997 and air pollution data since 1968 in Taiwan to estimate risks of 30-year PM2.5 exposures on AdLC. Cases were all AdLC, while references were all non-AdLC. Individuals’ 30-year PM2.5 exposures were estimated by PM2.5 levels at their residence for 30 years prior their diagnosis dates. We applied multiple logistic regression analyses to estimate PM2.5 exposures on incidence rate ratios (IRRs) between cases and references, adjusting for sex, age, smoking, cancer stage, and EGFR mutation. Elevation in annual ambient PM2.5 concentrations since 1968 were associated with increase in annual age-adjusted AdLC incidence since 1997. AdLC incidences were higher among females, nonsmokers, the elderly aged above 65, cases of stages IIIB to IV, and EGFR mutation. Study subjects’ PM2.5 exposures averaged at 33.7 ± 7.4 μg/m3 with 162 ± 130 high PM2.5 pollution days over 30 years. Multiple logistic models showed an increase in 10 μg/m3 of PM2.5 exposures were significantly associated with 1.044 of IRR between all AdLC and all non-AdLC cases during 2011–2020. Our models also showed that females and nonsmokers and adults less than 65 years had higher IRRs than their respective counterparts. Restricted analyses showed similar effects of PM2.5 exposures on IRRs between stage 0-IIIA and IIIB-IV cases and between EGFR+ and EGFR- cases. Long-term exposures to PM2.5 over 30 years were associated with elevated risks of AdLC against non-AdLC, regardless of gender, age, smoking status, cancer stage, or EGFR mutation. [Display omitted] •We applied visibility-based backcasting method to estimate individual PM2.5 exposure.•This nationwide case-referent study applied 52-year exposure and 24-year cases.•Adenocarcinoma lung cancers in Taiwan are increased by PM2.5 exposures since 1968.•Such associations were found in both duration and intensity of PM2.5 exposures.